ANALlSIS ERROR PENGUKURAN KONDUKTIVITAS PANAS MULSA LlMBAH PADAT ORGANIK: SEKAM PADI - Diswandi Nurba; Wahyu Purnama; Warji Warji (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT The objective of this paper is to analyze measurement error of heat conductivity of organic solid waste (paddy chaf). Error analyze is to obtain accuration of the measured result. Visual Basic Applications (VBA) on excel was used in simulation. The result showed that heat conductivity of paddy chaf is 0,501 W/mK with error 0,00936 W/mK. Voltage tolerance value gives highest effect on total error. Diterima: 9 Mei 2007, Disetujui: 24 Mei 2007